METODE PEMAHAMAN HADIS (KAJIAN PERDEBATAN HADIS TENTANG MAYIT DISIKSA KARENA TANGISAN KELUARGA) - Amrin Amrin; Miftahul Huda (Ushuluna: Jurnal Ilmu Ushuluddin, 2021)
This research departs from the problem regarding the debate of the scholars about the hadith of the tortured deceased because of the cries of his family, whether it is Saheeh or dhaif. The authors conclude that the results of the scholars’ understanding of the hadith vary: those who based on textual (text), and the other hand, those who understand the hadith with the asbab al-wurūd hadith, the situation, and conditions as well as the purpose, ensuring the meaning of the word in the hadith. With this understanding, there is a difference in opinion of the scholars regarding the hadith about the deceased being tortured because of the crying of the family. Differences occur because of using different approaches, methodologies, and ijtihad. So that some say that the hadith is authentic and some scholars say dhaif on the basis of their respective evidence. Hujjah in the form of narrators, eyes, and an understanding of the hadith eyes and asbabul wurud. The method used by the scholars in arguing about the hadith is by using the textual method, observance of the hadith, and asbab al-wurūd. So that the scholars used an approach to unifying differences with three approaches, namely the al-jam'u, takhyir, and tarjih methods.